The ethical and educational aspects of Abu Firas al-Hamdani\s poetry in The Roman Families Rhetorical descriptive study (320-357H) - Abdul Sattar Abdul Wahab Ayoub Osman (Tanjong Malim, 2020)
The ethical and educational aspects of Abu Firas al-Hamdani\s poetry in The Roman Families Rhetorical descriptive study (320-357H) by Abdul Sattar Abdul Wahab Ayoub Osman